Cell phone testing and fundamental scientific research. - Lin, James C.
There is a lack of scientific consensus on experimental studies that provide clear evidence either refuting or supporting the cancer induction or promotion potential of RF and microwave radiation from cell phones. The uncertainties persist, in part, because of the limited number and scope of studies that have been undertaken. There is a concern that an established effect from wireless radiation, even small, could have a considerable impact in terms of public health. The author discusses these issues.
Keywords: Biological effects of electromagnetic radiation; Land mobile radio cellular systems; Electromagnetic radiation effects; Occupational health and safety; Human health and safety; Research and development planning; Protocols; Research design; Risk analysis; Standards